Pt/Al-SBA-15 catalysts for hydrocracking of C-21-C-34 n-paraffin mixture into gasoline and diesel fractions - Seo, Myung-gi; Lee, Dae-Won; Lee, Kwan-Young; Moon, Dong Ju (ELSEVIER SCI LTD, 2015)
In this study, a Pt-loaded mesoporous aluminosilicate (Pt/Al-SBA-15) was optimized as a catalyst for the hydrocracking of Fischer-Tropsch waxes, for which n-paraffin wax in the C21-34 range was used as a model reactant. Pt/Al-SBA-15 was more active than a Pt-loaded microporous zeolite (Pt/b-zeolite) in producing gasoline-range products from n-paraffin wax. Hydrocracking over Pt/Al-SBA-15 occurs via a bifunctional mechanism, the activity of which was correlated closely with the density (concentration) of strong acid sites and total exposed Pt surface area. The reaction was more noticeably promoted at the Bronsted acid sites, rather than at the Lewis acid sites, of Al-SBA-15. The highest gasoline yield (72.8%) was achieved with the catalyst comprised of 0.5 wt.% Pt and Al-SBA-15 with Si/Al molar ratio of 14.5. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: FISCHER-TROPSCH WAXES; SOLID ACID CATALYSTS; MIDDLE DISTILLATE; HEAVY OIL; HYDROISOMERIZATION; SELECTIVITY; ZIRCONIA; SILICA; CONVERSION; REDUCTION